Identification of Causal Relationships between Foreign Direct Investment and Foreign Trade Patterns in Poland - Salamaga, Marcin (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2015)
In the literature there are studies that analyse the impact of foreign direct investment on changes in the pattern of comparative advantage, and on the structure of foreign trade. On the other hand, there are also possible feedback loops, in which the evolution of the pattern of comparative advantage, or the transformation of the structure of foreign trade influences foreign direct investment. So we can ask what the role they have in creating the interactions between variables, or which of these relationships are statistically significant and what is the direction of the impact of variables. The results of Granger causality test can help answer these questions. The aim of this paper was to find causal relationships between foreign direct investment and the variables representing the competitiveness of Polish foreign trade. The study employed vector autoregression models and Granger causality test.